The Artistic picture in the sunset garden diwan by Ghazi Abdul Rahman Al-Gosaibi - Abudabeel, Sultan Saeed Muraia (Journal of Humanities & Social Sciences, 2021)
The poet "Ghazi bin Abdul Rahman Al- Gosaibi" is considered one of the figures of Saudi literature in particular, and Arab literature in general. I tried to reach in this book the literary depth, which made with Mina Al- Qusaibi broadcast his book the juice of an experience that was not a little in literature, and the same is true that the exploration of the literary depths that we discussed in this book, did not come to Al- Qusaibi that he is only a poet, but that he combined politics And literature, and this is what brings us to the beautiful literary eras, when the poet combined literature and politics, for example: to be a minister, or a prince, in the Abbasid era, for example, and a poet at the same time. When you stand with the Diwan of Sunset Garden, you can stand with Al- Qusaibi’s biography, as if he wanted to summarize the stations of his life, and his lost companions, and he is fully aware that, today, he laments those who lose his comrades, and tomorrow he laments. In this research, we found out how political life played a major role in making Al- Gosaibi see things that the public did not see. Had it not been that he came out for us with a literary- political book he called "In My Humble Opinion", which is not the field of our research now, but the follower of Al- Qusaibi’s production knows how much he had a view of life different from that of the ordinary human being. As for the title of the Diwan, Al- Gosaibi combined two opposites with it. It is as if he wanted to summarize great things in himself, through this title, as he came at the beginning “The Garden” and it is known to us that the garden denotes greenery and psychological comfort; As it bears a natural divine beauty, it restores calm to the human soul. As for “sunset” it indicates the end, indicates the end of the day, and comes after sunset the night, and the worries and pain that the poets endured since the pre- Islamic era. As for Al- Qusaibi: He tried to say through the title of the Diwan: His condition is like that of the owner of any house who takes care of him and makes him in the best condition, and takes care of his garden, but at the end he sits in this garden waiting for his day.